Las TICS y su influencia en el desarrollo de la lectura crítica en los estudiantes del sexto año de Educación General Básica de la Unidad Educativa Franciscana “San Andrés Quitumbe” - Granada Tipán, Rafael Alexander (2022)
In this research report, there are two variables that are related to each other as the subject of study, "The incidence of the use of ICT and the development of Critical Reading of the Educational Unit “San Andrés Quitumbe” students; in addition, the objective of this is to develop a Technological Didactic Guide aimed to improve the level of development of critical reading in sixth-year students, through didactic strategies that allow a solution to the problem mentioned. Therefore, it presents a quantitative methodology with the deductive method, based on existing theories that determine a variable of cause and effect, in order to prove the theory of reality and describing it statistically to show the relationships between the variables that allow them to be operationalized, becoming an applied type of research. This proposal has allowed students to exceed expectations in each of the meetings, motivating them to develop skills for the development of critical reading with its different levels, such as literal, inferential and critical evaluation established in the guide. Besides critical thinking and the evaluation of texts have been developed in an innovative way, according to the social context, which has allowed showing up the pleasure for reading that the reader should have. Carrying out an analysis of a text that enriches their knowledge by delighting in reading and issuing a value judgment, too.